Workplace Ostracism and Employee Performance: The Interactive Roles of Leader-Member Exchange and Gender - Suherman, Enjang; Pranata, Rengga Madya; Sumarni, Neni; Suroso, Suroso (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study investigates the impact of workplace ostracism on employee performance, focusing on the role of Leader-Member Exchange (LMX) as a moderator and the influence of gender as a sub-moderator. Research Methodology: Using a quantitative explanatory design, this study surveyed 384 frontline employees from the retail, education, healthcare, hospitality and restaurant, finance, and public service sectors in Indonesia to test the hypotheses. Questionnaire data were analyzed using Hayes’ PROCESS macro model 3. Results: The findings show that workplace ostracism has a significant negative impact on employee performance. Additionally, the quality of the leader-member exchange relationship serves as a protective mechanism that reduces the negative effects of social exclusion, with a stronger influence on female employees. Gender has been shown to play an important role in moderating the relationship between leader-member exchange and workplace ostracism on performance. Conclusions: This study concludes that the leader-member exchange relationship can reduce the negative impact of workplace ostracism, with gender playing a significant role in strengthening or mitigating this impact. Limitations: This study is limited to the service sector in Indonesia; future research can expand to other sectors and include additional variables to enrich the findings. Contributions: This study provides valuable insights for organizations in creating healthy relationships between supervisors and subordinates and considering gender factors when designing more effective employee management policies, particularly in the service sector, which demands intensive social interaction. This study also opens avenues for further research in various sectors and cultural contexts.